Прогнозування ускладнень вагітності та пологів у жінок групи ризику з переношування вагітності - Богуславська, Наталія Юріївна; Boguslavskaya, N. Yu. (Запорізький державний медичний університет, 2018)
У дисертаційній роботі на підставі комплексного дослідження параметрів клінічного, лабораторного та інструментального обстеження виявлено, що при вагітності терміном більше ніж 41 тиждень спостерігається достовірно більша кількість ускладнень під час пологів. Жінки групи ризику з переношування вагітності мають відмінності в гормонопродукуючій функції фетоплацентарного комплексу, що виявляється в менш інтенсивному наростанні вмісту гормонів у крові порівняно з фізіологічним перебігом вагітності: у ІІІ триместрі вагітності рівень кортизолу, прогестерону, естріолу й плацентарного лактогену був достовірно нижче від рівня аналогічних гормонів у контрольній групі в ті самі терміни гестації. Оцінювання ризику методом ROC-аналізу та логістичної регресії надає змогу розрахувати критичне значення рівня гомоцистеїну (9,5 мкмоль/л), що асоціюється з високим ризиком розвитку ускладнень (площа під ROC-кривою становить понад 90%). Запропонований метод прогнозування ускладнень за рівнем гомоцистеїну сироватки має досить високу чутливість (87,5%), специфічність (84,21%), позитивну й негативну передбачувану значущість (85,37% і 86,49% відповідно) щодо діагностики високого ризику розвитку ускладнень у групі ризику переношування вагітності. The thesis based on a comprehensive study of parameters of clinical, laboratory and instrumental examination, it was found that during prolonged pregnancy, there were significantly more complications of pregnancy and childbirth, such as: premature rupture of membranes, weakness of labor, maternity injuries, postpartum hemorrhage, fetal distress, operative delivery (vacuum extraction and caesarean section) that leads to increasing number of bed-days.Women at risk for prolonged pregnancy were differed in the hormone-producing function of the fetoplacental complex, manifested by a less intense increase in the hormone content in the blood compared with the physiological pregnancy: in the third trimester of pregnancy the level of cortisol, progesterone, estriol and placental lactogen were significantly lower than the level of similar hormones in the control group at the same gestation period, that is a manifestation of placental insufficiency, fetal trophiс function, and determines negative pathophysiological background for the development of complications in the perinatal period on the background of prolonged pregnancy. The level of homocysteine reliably positively associated with the development of complications of the birth period and perinatal lesions. Risk assessment by ROC analysis and logistic regression allows to calculate the critical value of homocysteine level (9.5 mkmol/L), which is associated with a high risk of complications (the area under the ROC curve is more than 90%). The proposed method for predicting the complications on the level of serum homocysteine has a high enough sensitivity (87.5%), specificity (84.21%), positive and negative predictive significance (85.37% and 86.49%, respectively) for diagnosis of a high risk of complications of prolonged pregnancy.Through a comprehensive statistical analysis, a discriminant model of the dependence of the development of perinatal complications in women at risk of prolonged gestation from high PI in umbilical artery, homocysteine > 9.5 μmol/L, STV less than 5 ms, and hormonal profile of fetoplacental complex was obtained. The model takes into account not only a separate factor, but their combined contribution to the development of complications in women at risk of prolonged pregnancy. The proposed model has good prognostic properties, allows timely and accurate diagnosis of gestational disorders, stratification of pregnant women in accordance with the risk group (risk 1 – the probability of development of complications more than 90%, risk 2 – the probability of development of complications, less than 10%, respectively). The use of this model in practice helps to optimize prediction, to carry out preventive measures in pregnant women, to review the plan of observation of the pregnant woman in the direction of timely hospitalization, the appointment of medicines and improve perinatal effects.
Predicting complications of pregnancy and delivery in women with risk of prolonged pregnancy
Keywords: переношена вагітність; гомоцистеїн; фетоплацентарний комплекс; ускладнення; перинатальний період; прогнозування; prolonged pregnancy; homocysteine; fetoplacental complex; complications; perinatal period; prognosis